1990
DOI: 10.1021/np50072a002
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic Agents, 177. Isolation and Structure of Phyllanthostatin 6

Abstract: The isolation and structural elucidation of a new Phyllanthus glycoside, phyllanthostatin 6 [7], was summarized. Phyllanthostatin 6 [7] was isolated from the roots of Phyllanthus acuminatus (Euphorbiaceae) and was found to inhibit (ED50 = 0.35 micrograms/ml) growth of the murine P-388 lymphocytic leukemia cell line. Two other new constituents were shown to be didesacetylphyllanthostatin 3 [9] and descinnamoylphyllanthocindiol [10]. Structure determinations were achieved employing hrfabms and 2D-nmr spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…Studies with P. niruri have found flavonoids such as quercetin and kaempferol (El-Mekkawy et al, 1995), lignin glycosides called phyllanthostatin A, 1 and 2 (Pettit, Schaufelberger, 1988;Pettit et al, 1990), ellagitannins such as geraniin and furosin (Miguel et al, 1996), niruroidine (Quian-Cutrone et al, 1996), lignans as nirtetralin A and B (Wei et al, 2012) among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with P. niruri have found flavonoids such as quercetin and kaempferol (El-Mekkawy et al, 1995), lignin glycosides called phyllanthostatin A, 1 and 2 (Pettit, Schaufelberger, 1988;Pettit et al, 1990), ellagitannins such as geraniin and furosin (Miguel et al, 1996), niruroidine (Quian-Cutrone et al, 1996), lignans as nirtetralin A and B (Wei et al, 2012) among others.…”
Section: Introductionmentioning
confidence: 99%
“…The aqueous extract inhibits reverse transcriptase in the human immunodeficiency virus type 1 (HIV-1-RT) (Ogata et al, 1992; El-Mekkawy et al, 1995;Notka, Meier, Wagner, 2003). However, other studies have been conducted in an attempt to prove several other biological activities, such as analgesic action (Miguel et al, 1996;Santos et al, 1995;Santos et al, 2000), anti-tumor activity in different cell lines (Powis, Moore, 1985;Pettit, Schaufelberger, 1988;Pettit et al, 1990;Rajeshkumar, Kuttan, 2000), antioxidant effects in preventing gastric ulcers (Bandyopadhay, Pakrashi, 2000), anti-inflammatory (Ignácio et al, 2001;Kiemer et al, 2003) and anti-malaria activity (Muñoz et al, 2000) and reduced plasma lipid levels in rats (Khanna, Rizvi, Chander, 2002). It also exhibits abortive and purgative action in large doses (Martins et al, 1994).…”
mentioning
confidence: 99%
“…Further column chromatography (CC) over Diaion HP20SS, Sephadex LH-20 and silica gel, followed with semipreparative HPLC purification of the MeOH extract yielded five new compounds (1)(2)(3)(4)(5), together with two known ones. The known compounds were elucidated as jasminoside (6) 6 and jaslanceoside B (7) 7 by comparison of their spectroscopic data with reported literature values.…”
Section: Resultsmentioning
confidence: 99%
“…Previous chemical studies on this genus have revealed the occurrence of flavonoids, alkaloids, sesquiterpenoids, triterpenoids, lignans, and tannins. [1][2][3][4][5] Among them, some sesquiterpenoids exhibited potent antiviral activity against coxsackie virus B3 (CVB3), 4 and inhibition of the growth of murine P-388 lymphocytic leukemia cell line. 5 P. cochinchinensis, a shrub up to 3 m height, is mainly growing in the montane sparse forests, forest margins, scrub on slopes, and wastelands of the southern part of China.…”
Section: Introductionmentioning
confidence: 99%
“…Many biological and pharmacological functions such as anticancer, cardioprotective, hepatoprotective, antiangiogenic, antioxidant, antisemicarbazide-sensitive amine oxidase, antihypertensive (1)(2)(3)(4)(5)(6)(7)(8) antibacterial [9], antiinflammatory, antimutagenic, antioxidant (Scartezzini et al, 2006[10]), antipyretic, antitumour [11]chemopreventive [12]and hepatoprotective activities have been reported in both in vitro and in vivo. The antitumor effect of Phyllanthus species was first verified by its activity against murine B-16 melanoma and P-388 leukemia.…”
Section: Imentioning
confidence: 99%